Evaluation of the fracture resistance of premolars with extensive and medium cavity preparations restored with direct restoring systems - Larissa Fernanda Pottmaier; Ludmilla de Azevedo Linhares; Luiz Narciso Baratieri; Luiz Clovis Cardoso Vieira (Wolters Kluwer Medknow Publications, 2018)
Context: Studies have been conducted to measure the fracture resistance of restored teeth with the current restorative materials. However, most of those studies disregard the cavity size as an influencing variable. Aims: To evaluate the fracture resistance of prepared and restored maxillary premolars with medium and large preparations. Materials and Methods: Seventy superior and sound premolars were randomly divided: G1 (control) - sound tooth; G2, G3, and G4 received a Class II mesial-occlusal-distal (MOD) preparation with an occlusal box width 1/3 of the intercuspal distance, and were restored with Filtek Z350 XT, IPS Empress Direct, and Charisma Diamond, respectively; G5, G6, and G7 received a Class II MOD preparation with an occlusal box width 2/3 of the intercuspal distance, and were restored with Filtek Z350 XT, IPS Empress Direct, and Charisma Diamond, respectively. After storage in water, at 37°C, the specimens were subjected to a fracture test under compression in a universal testing machine where the loads were applied vertically and at a speed of 0.5 mm/min. Statistical Analysis Used: Data were analyzed with two-way ANOVA and Tukey's multiple comparison post hoc test (P < 0.05). Results: G1 presented a fracture resistance significantly higher (P = 0.005) than any other experimental groups. Among the experimental groups, only G5 showed a significantly low fracture resistance (P = 0.019) when compared to the other groups. For the other resins, the change in intercuspal distance from 1/3 to 2/3 the intercuspal distance did not significantly reduce the fracture resistance (P > 0.05). Conclusions: The cavity preparation weakens the remaining tooth structure; however, its resistance could be partially restored using direct adhesive restorations.